2018
DOI: 10.1007/s10926-018-9776-8
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Developed with the Intervention Mapping Protocol in Work Disability Prevention: A Systematic Review of the Literature

Abstract: Purposes Intervention mapping (IM) is a protocol for developing effective behavior change interventions. It has been used for 10 years to develop work disability prevention (WDP) interventions, but it is not known to what extent and with what success. The main objective of this study was to review the effectiveness of these interventions. Secondary objectives were to review their fidelity to the IM protocol, their theoretical frameworks and their content. Methods A search strategy was conducted in MEDLINE, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 64 publications
0
31
0
4
Order By: Relevance
“…IM is one of the most comprehensive systematic approaches for the development of theory and evidence-based behavior change interventions, and it is a framework that is characterized by a participative approach involving the relevant stakeholders [29,30]. This framework has been used regularly in the development and implementation of both cancer-related [31] and work-related interventions [32][33][34][35]. The IM framework consists of six consecutive steps, with the results of each step guiding the subsequent one: step 1, needs assessment; step 2, formulating objectives using a logic model of change; step 3, selecting theories and practical strategies; step 4, developing the intervention; step 5, planning for program adoption and implementation; and step 6, planning for evaluation [30].…”
Section: Methodsmentioning
confidence: 99%
“…IM is one of the most comprehensive systematic approaches for the development of theory and evidence-based behavior change interventions, and it is a framework that is characterized by a participative approach involving the relevant stakeholders [29,30]. This framework has been used regularly in the development and implementation of both cancer-related [31] and work-related interventions [32][33][34][35]. The IM framework consists of six consecutive steps, with the results of each step guiding the subsequent one: step 1, needs assessment; step 2, formulating objectives using a logic model of change; step 3, selecting theories and practical strategies; step 4, developing the intervention; step 5, planning for program adoption and implementation; and step 6, planning for evaluation [30].…”
Section: Methodsmentioning
confidence: 99%
“…It is unusual for IM studies focusing on return to work interventions to report on all six steps of the IM process, particularly Step 5. Fassier et al [27] found that this step was insufficiently developed in any previous studies for it to be included in their review of fidelity to the IM protocol. Although we focus in this paper on steps 1-4 that describe the process for intervention development, steps 5 (implementation) and 6 (feasibility testing) have also been completed and these will be reported separately.…”
Section: Discussionmentioning
confidence: 99%
“…IM is a framework for developing effective theory-and evidence-based behaviour change interventions [23,24]. IM was developed for, and is widely used in health promotion, but has also been used in rehabilitation, for example in the management of osteoarthritis and back pain [25] and stroke [26] as well as in work disability prevention [27]. The IM framework was first used in work disability prevention in 2007.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of the planning group represents faithfully the intersectoral nature of the problem. Despite the importance of the participative process in the IM protocol, only a few studies using this protocol in the field of cancer ( 29 ) and in the field of RTW ( 65 ) reported the association with a complete planning group from the needs assessment phase. This shortcoming has been discussed as a potential cause for the lack of relevance, acceptability, and/or efficiency of the studies developed ( 29 ).…”
Section: Discussionmentioning
confidence: 99%